QuantiFERON‐TB Gold conversion is not uncommon in patients with psoriasis undergoing anti‐tumour necrosis factor‐α therapy. (1st November 2020) - Megna, M.; Ruggiero, A.; Ferrillo, M.; Fabbrocini, G.
Abstract: Linked Article:  Ya et al. Br J Dermatol 2020; 182 :800–802 .